Determinants Related to Low Back Pain Complaints in Rice Farmers in Pantilang Village, North Bastem District Kabupaten Luwu - Sombolinggi, Yeltiani; Adam, Arlin; Alim, Andi (Green Publisher Indonesia, 2025)
Low back pain is pain felt in the lower back that originates from the spine, muscles, nerves, or other structures in the area. Back pain can be caused by diseases or disorders that originate outside the lower back, such as diseases or disorders in the waist. This study aims to identify the determinants related to low back pain complaints in rice farmers in Pantilang Village, North Bastem District, Luwu Regency in 2023. The research employed a quantitative observational analytical study with a cross-sectional approach. The population consisted of all rice farmers in Pantilang Village, and based on the Slovin formula calculation, a total of 37 samples was obtained using simple random sampling technique. Data collection instruments included questionnaires and REBA sheets, with Chi-square test analysis using SPSS 20 software. The study results showed significant relationships between work posture and low back pain complaints (p=0.002), workload (p=0.000), duration of work (p=0.018), and exercise habits (p=0.004). The conclusion indicates that there are significant relationships between work posture, work duration, workload, and exercise habits with low back pain complaints in rice farmers in Pantilang Village, North Bastem District, Luwu Regency in 2023.